Full-length transcriptome sequencing reveals the molecular mechanism of monoterpene and sesquiterpene biosynthesis in Cinnamomum burmannii - Hou, Chen; Zhang, Qian; Xie, Peiwu; Lian, Huiming; Wang, Yingli; Liang, Dongcheng; Cai, Yanling; He, Boxiang (Frontiers in Genetics, 2023)
Essential oil of Cinnamomum burmannii is rich in monoterpenes and sesquiterpenes and is widely used in cosmetics and medicines. Knowledge about the enzymes that catalyze the formation of monoterpenes and sesquiterpenes in C. burmannii is insufficient. Therefore, anatomy observation of C. burmannii at the four developmental stages (7 days, CBS1; 14 days, CBS2; 21 days, CBS3, and 28 days, CBS4) were conducted to elucidate the origins of essential oil production. Twelve full-length transcriptomes of C. burmannii leaves at the four stages were generated using Oxford Nanopore Technologies. GC-MS analysis revealed 15 monoterpene and sesquiterpenes dramatically increased from CBS1 to CBS4. A weighted correlation network analysis (WGCNA) in association and differentially expressed genes across four developmental stages were performed. A total of 44 differentially expressed genes (DEGs) were involved in terpenoid syntheses during leaf development. Among them, the DEGs of the mevalonate acid (MVA) pathway were predominantly expressed at CBS1, while those of the 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway showed increased expression from CBS2 to CBS4. Besides, fourteen genes were associated with monoterpene synthesis and nine with sesquiterpene synthesis. Functions of these DEGs were further predicted with regard to gene expression profile and phylogenetic relationship with those characterized in previous studies. In addition, 922 long noncoding RNAs (lncRNAs) were detected, of which twelve were predicted to regulate monoterpene and sesquiterpene biosynthesis. The present study provided new insights the molecular mechanisms of monoterpenoid and sesquiterpenoid syntheses of C. burmannii.